2020
DOI: 10.1038/s41598-020-60789-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extracellular medium conductivity on cell response in the context of sub-microsecond range calcium electroporation

Abstract: In the present study, we report the effects of extracellular medium conductivity on cell response in the context of sub-microsecond range (100 ns-900 ns) electroporation, calcium electroporation and cell size. The effects of 25 ns and microsecond range (100 μs) pulses were also covered. As a model, three different cancer cell lines of various size (C32, MCF-7/DX and MC38/0) were used and the results indicated different size-dependent susceptibility patterns to the treatment. The applied pulsed electric field (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…However, the electrophoretic component of longer (microsecond) pulses is much higher compared to ultra-short pulses; therefore, a similar treatment outcome indicates that passive diffusion of calcium was the dominant mechanism of delivery through a permeabilized membrane. Indeed, calcium is a small ion, and thus passive diffusion is sufficient to ensure significant electrotransfer, even in the nanosecond range when the electrophoresis influence is negligible [34]. We have shown that during supra-electroporation, when the pulse duration is significantly shorter than the polarization time, electric field strength should be increased several-fold to trigger the same permeabilization rates as in the case of longer pulses.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the electrophoretic component of longer (microsecond) pulses is much higher compared to ultra-short pulses; therefore, a similar treatment outcome indicates that passive diffusion of calcium was the dominant mechanism of delivery through a permeabilized membrane. Indeed, calcium is a small ion, and thus passive diffusion is sufficient to ensure significant electrotransfer, even in the nanosecond range when the electrophoresis influence is negligible [34]. We have shown that during supra-electroporation, when the pulse duration is significantly shorter than the polarization time, electric field strength should be increased several-fold to trigger the same permeabilization rates as in the case of longer pulses.…”
Section: Discussionmentioning
confidence: 88%
“…Cell suspension was kept on ice before electroporation and then pulses were delivered in a cuvette (Bio-Rad) between 1 mm gap parallel plate aluminum electrodes. Electroporation protocols were also combined with CaCl 2 (Sigma-Aldrich) in a 2 mM concentration, based on our previous study [34]. Calcium chloride solution was prepared in the same buffer as for electroporation alone.…”
Section: The Effect Of Pef and Extracellular Ca 2+mentioning
confidence: 99%
“…As indicated in Table 3.1, the device was successfully used to investigate the nsPEF effects, which resulted the proposal of new treatment methodologies and non-viral gene delivery methods proof of concept (Novickij, Rembialkowska, et al 2020;Ruzgys et al 2018;Novickij, Zinkevičienė, Perminaitė, et al 2018;Novickij, Stanevičienė, et al 2020;Novickij, Zinkevičienė, Valiulis, et al 2018;Novickij, Zinkevičienė, Stanevičienė, et al 2018;Novickij, Česna, et al 2019), which confirmed, that nsPEF bursts can be used for eradication of bacteria. The developed square-wave systems application has also included the research in MHz pulse repetition frequency range (Ruzgys et al 2019;Pakhomov et al 2019).…”
Section: The Application Of Prototype System For Electroporationmentioning
confidence: 84%
“…The percentage of stained cells was shown in the table, after which the intensity of the staining was estimated. The intensity of the immunohistochemical staining was assessed as (-) negative (no reaction), (+) weak, (++) moderate and (+++) strong [ 34 ].…”
Section: Methodsmentioning
confidence: 99%